If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7m = 6m + -6 Reorder the terms: 7m = -6 + 6m Solving 7m = -6 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. 7m + -6m = -6 + 6m + -6m Combine like terms: 7m + -6m = 1m 1m = -6 + 6m + -6m Combine like terms: 6m + -6m = 0 1m = -6 + 0 1m = -6 Divide each side by '1'. m = -6 Simplifying m = -6
| 2.1=4.3-1.1w | | 3(2+y)+3=12 | | 4x+2=4(x-6) | | x+13=4x-42 | | y=(50)x+b | | c/2-3.2=26.8 | | -2z=-z+9 | | -5(x-2)+8x=5x-6 | | 36+7n=6(n+7) | | 13=7+21t-16t^2 | | 10-4j-7=-9-7j | | 2x+6=3+6x-7 | | -7625+185t=0 | | 2q=18.92+6.3q | | 13.9j-9.71-8.7=9.43+16.3j | | -4y=-3y-10 | | 7x+4(x-5)=3(x+2)-5 | | 8x-3y=14fory | | 2x+5+6x-1=90 | | 3+10q=6+9q | | 3/4z=-5+1/2 | | 19.03+11.2y=5.1y-17.59-9.13 | | 4(-6x+1)=20-8x | | 335=5x^3 | | 8x+5-2x=-(5x-x) | | 3/4z=-5.5 | | 14.7t-5.79=15t | | 9h-(2h-4h+1)=38-2h | | 15.7g+18.66+7.2g=19.5g-13.64 | | -3(5a+6)=-5a+22 | | 0.7x-0.1=0.6x+2 | | 15x=2(1+9x) |